(untitled) (diségno, 2025)
A professor is delivering a lecture in a university classroom. It is an ‘intermediate’ lecture for an ‘intermediate’ year of study. The students are already familiar with the academic path, the subject matter –having learned most of the technical terminology– and with the professor himself. Though the lesson is technical in nature, it does not introduce particularly advanced content. [read more]